An Interdisciplinary Approach to Interior Design in the Context of Environmental Protection Awareness: Relation between Interior Architecture and Environmental Engineering - Deniz Demirarslan; Kazım Onur Demirarslan (Doğal Afetler ve Çevre Dergisi)
Developments in the fields of science and technology, especially since the last half of the 20th century, reveal new research and approaches in the world. In presenting the results of these researches and approaches, it is not enough to think and evaluate in a single field today. It is not possible to examine newly developed areas through a single disciplinary approach. It is the use of other disciplines to support these thoughts and evaluations. In this context, interdisciplinary approach is needed. Today, as a result of the advancement in technology and science, the development of construction technology and changes in the living necessities; designing architectural spaces that are more liveable, transferable to future generations, and causing less damage to the environment during their construction and use is now regarded as a design trend. Hence, interior architecture alone is not enough to create environmentally sensitive space. In this process, it is necessary to receive support for environmental engineering issues. In this study, it is aimed to handle both the interior architecture, a discipline of design, and the environmental engineering, a discipline of engineering with an interdisciplinary approach to find common grounds and to determine the contribution of environmental engineering to interior architecture. In the scope of the study, firstly, the interdisciplinary study features were mentioned, the related disciplines were examined and the common grounds between the two disciplines were explained with examples.